(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the new national idea of our country - the essence of the Third Renaissance, the stages of this process in Uzbekistan, the work being done by the government on the current problems in school chemistry education and their solutions and the requirements for modern teachers during the Third Renaissance.